Antecedents of Accounting Understanding with Interest as a Moderating Variable in STIE Pembangunan Tanjungpinang Students - Helen; Fauzi; Alamsyahbana, Muhammad Isa; Ranat Mulia Pardede; Charly Marlinda (Future Science, 2024)
This study aims to examine the influence of Emotional Intelligence, Intellectual Intelligence, and Spiritual Intelligence on Accounting Understanding, as well as the potential of Interest as a moderating factor. The results indicate that all three types of intelligence significantly influence accounting understanding partially. Additionally, Interest can moderate the influence of Emotional Intelligence and Spiritual Intelligence on Accounting Understanding, but not Intellectual Intelligence. These findings provide additional insights into the factors influencing accounting understanding among accounting students.